Stability of corn cultivars under different planting dates and locations in Minas Gerais, Brazil - de Souza, Francisco Ronaldo Sarmanho; Ramalho, Magno Antonio Patto; de Oliveira, Antônio Carlos; Sans, Luis Marcelo Aguiar (Pesquisa Agropecuaria Brasileira, 1991)
In order to verify the extent and similarity of the interactions cultivars x seeding dates, and cultivars x locations, aiming to identify stable materials concerning environmental changes, some trials were carried out at Sete Lagoas and Lavras, MG, Brazil, in 1987/88. On each date distinct competition trials in a randomized block design with three replications were made. The interaction cultivar x planting date was significant, but less than the interaction cultivar x location, indicating the importance of evaluating more locations intead of increasing number of dates at the same location. The interaction cultivar x planting dates resulted mainly from manifestation of genetic differences within each planting date. Correlations between locations and different planting dates were low, suggesting that the correlation is predominantly complex. The estimates of correlations of stability parameters indicate it is possible to identify stable and responsive cultivars. The cultivar BR 201, with higher average yield, indicates its responsiveness, but with low stability under unfavorable environments. BR 350 and CMS 37 showed stability under unfavorable environments but with low yields and little responses to environmental improvement.